Analyzing the adoption of artificial intelligence by Moroccan university teachers: Key insights and implications from the UTAUT model - Hicham, OUZIF; Hayat, EL BOUKHARI; Maryem, EL ACHABI; Ouail, CHAHBOUNI; Mohamed, ES-SANOUN; Nacer, MAHOUAT; Salma, BAKKALI (Edelweiss Applied Science and Technology, 2025)
This study examines the factors influencing the adoption of artificial intelligence (AI) by Moroccan university teachers, using the UTAUT model. A questionnaire was distributed to 75 professors at Sidi Mohamed Ben Abdellah University in Fez, and the data were analyzed using structural equation modeling (SEM). The results show that facilitating conditions and social influence are the primary determinants of AI adoption intention. In contrast, performance expectancy and effort expectancy had no significant impact. This research highlights the need to enhance technological infrastructure and implement targeted training programs to foster AI integration in Moroccan higher education. It contributes to the literature by extending the UTAUT model to an underexplored cultural and educational context while providing practical recommendations for overcoming barriers to AI adoption in developing countries.